The dog master - Cameron, W. Bruce (Forge, 2015)
"Set against the most dramatic time in our species' history, The Dog Master tells the story of one tribe's struggle for survival and one extraordinary man's bond with a wolf-a friendship that changed mankind forever... Thirty thousand years ago, ice was storming the planet. Among the species forced out of the trees and onto the steppes by the advancing cold was modern man, who was both predator and prey. No stranger to the experiences that make us human-a mother's love and a father's betrayal, tribal war and increasing famine, political intrigue and forbidden love, joy and hope and devastating loss-our ancestors competed for scant resources in a brutal landscape. Mankind stood on the cold brink of extinction...but they had a unique advantage over other species, a new technology-domesticated wolves. Only a set of extraordinary circumstances could have transformed one of these fierce creatures into a hunting companion, a bodyguard, a solider, and a friend. The Dog Master by W. Bruce Cameron is an evocative glimpse of prehistory, an emotional coming of age saga, a thrilling tale of survival against all odds, and the exciting, imaginative story of the first dog"--